Ulil Abshar Abdallah And His Attempts To Spread Liberalism In Indonesia - Andi Ridwan Abdul Rahim; Mohd Khairul Nizam Zainan Nazri; Kabiru Goje (Usuli Faqih Research Centre PLT, 2024)
Non-Indexed Publication